2007
DOI: 10.1051/alr:2007020
|View full text |Cite
|
Sign up to set email alerts
|

Mobility and home-range use of Atlantic salmon parr over short time scales

Abstract: -This study performed in the Patapédia River (Québec, Gaspésie) was designed to examine the space utilization and mobility patterns of individual Atlantic salmon parr over short time scales with frequent detections of position. In August 2004, n = 7 radio-tagged Atlantic salmon parr were located every 20 min during 10 tracking periods chosen to take into account the dawn, day, dusk and night periods. Parr showed important inter individual variability in space utilization and mobility patterns, occupying large … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Recent studies have suggested that implanting small fish such as juvenile salmonids with transmitters weighing from 2 to 12% of body weight does not affect the swimming performance of fish (Brown et al, 1999;Robertson et al, 2003;Lacroix et al, 2004;Økland et al, 2004Økland et al, , Enders et al, 2007Ovidio et al, 2007). However, it has been suggested that the presence of a trailing whip antenna may sometimes cause changes in social status (Connors et al, 2002), predator avoidance (Adams Sedentary fish: remained in the same area since the previous capture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have suggested that implanting small fish such as juvenile salmonids with transmitters weighing from 2 to 12% of body weight does not affect the swimming performance of fish (Brown et al, 1999;Robertson et al, 2003;Lacroix et al, 2004;Økland et al, 2004Økland et al, , Enders et al, 2007Ovidio et al, 2007). However, it has been suggested that the presence of a trailing whip antenna may sometimes cause changes in social status (Connors et al, 2002), predator avoidance (Adams Sedentary fish: remained in the same area since the previous capture.…”
Section: Discussionmentioning
confidence: 99%
“…The 2 9 n = 5 fish were located during two 25-to 30-day tracking sessions that started on 20 February 2007 and on 22 May 2007. Tagged sculpins were located at least every day alternating between 9 and 12 h or 14 and 17 h. Fish were not tracked for the first 24-h period after their release to avoid biased observations that may reflect a traumatic state just after capture and tagging (Ovidio et al, 2007). Locations were made using a mobile FieldMaster radio receiver and a loop antenna (ATS Inc.) making sure to approach the site with the greatest possible precautions to avoid disrupting the fish.…”
Section: Radio-telemetry Studymentioning
confidence: 99%
“…Close tracking also indicated high variability among individuals in terms of both range size and habitat use. Subsampling of the mobility data obtained from Atlantic salmon parr (two and six observations out of 32/d) demonstrated a significant loss in precision and accuracy of estimates on mobility patterns and home ranges (Ovidio et al 2007). Frequent observations were therefore necessary to fully describe parr utilization of space.…”
Section: Discussionmentioning
confidence: 99%
“…With a larger sample size, the cost would have been less-frequent observations. However, the intensive radio-tracking methodology was used by Ovidio et al (2007) to investigate space utilization and mobility patterns of individual Atlantic salmon parr over short time scales with frequent detections of position, revealing that parr may be far more mobile and have larger home ranges than previously assumed. Close tracking also indicated high variability among individuals in terms of both range size and habitat use.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation